Signal Design for Communication Centric ISAC: State of Art and Future Aspects - Aimin TANG; Fan LIU; Weijie YUAN; Jie YANG; Shuhan WANG; Lan LAN; Xianxiang YU; Zhiyong FENG; Shi JIN (Leida xuebao)
Integrated Sensing And Communications (ISAC), a key technology for 6G networks, has attracted extensive attention from both academia and industry. Leveraging the widespread deployment of communication infrastructures, the integration of sensing functions into communication systems to achieve ISAC networks has emerged as a research focus. To this end, the signal design for communication-centric ISAC systems should be addressed first. Two main technical routes are considered for communication-centric signal design: (1) pilot-based sensing signal design and (2) data-based ISAC signal design. This paper provides an in-depth and systematic overview of signal design for the aforementioned technical routes. First, a comprehensive review of the existing literature on pilot-based signal design for sensing is presented. Then, the data-based ISAC signal design is analyzed. Finally, future research topics on the ISAC signal design are proposed.